Antiviral therapy and regression of liver fibrosis at chronic hepatitis B - D. T. Abdurakhmanov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2010)
The aim of review. Studying of effect of antiviral therapy on regression of fibrosis in chronic hepatitis B.Original positions. Article presents analysis of the largest investigations estimating effect of interferon α and nucleoside/nucleotide analogues on development of liver fibrosis. Decrease of severity of fibrosis (for prophylaxis of liver cirrhosis and hepatocellular carcinoma development) is one of the basic criteria of efficacy of treatment of chronic liver diseases. Now various strategies of influence on fibrosis are discussed, including elimination of etiological factor, suppression of inflammation and specific antifibrotic therapy.Conclusion. Successful antiviral therapy at chronic hepatitis B (continuous suppression of replication of virus and activity of inflammation in the liver) results in regression of fibrosis, including cirrhotic stage, and is associated with improvement of patients’ survival rate.